ANALISIS PERTENTANGAN PANDANGAN ANTARA GENERASI X DENGAN GENERASI MILENIAL TENTANG BUDAYA POPULER (Studi Semiotika Roland Barthes Pada Film My Generation) - Widia Ramadhanti; Dwi Rini Sovia Firdaus; Intan Trikusumaningtias (UNIVERSITAS PAKUAN, 2021)
This research aims to identify conflicting views between generation x figures with millennials in My Generation film that shows the dynamics of millennial life in the era of technological development and popular culture development interpreted through adegans and dialogues in adegans certain. This study uses a qualitative method with Roland Barthes's semiotic analysis which has the concepts of denotation, connotation and myth. Analysis of the whole adegan, six adegans have been taken that represent the conflicting views between x generation with millennial generation in the film my generation. The six adegans are analyzed through denotation and connotation and a myth appears in several adegans. The results of this study can be concluded that the conflict of views between generation x (as parents), and millennial generation (as children) towards popular culture, occurs because of differences in lifestyle and differences in the way in responding to the cycle of cultural movement.